Codrington College Barbados - Poyer, [John] (My University, 2012)
The buildings and grounds of the college. The surrounding landscape features palm trees, lawn and a large pond. On front, bottom right hand corner is inscription "Poyer photo". Codrington College, located in St. John, Barbados in the Caribbean is the oldest Theological College in the western hemisphere. The college is named after Christopher Codrington III (1668-1710). He was the son of a very prominent Barbadian, Christopher Codrington II, who was at one time Governor General of the Leeward Islands.
Landscape; black and white
Keywords: Theological seminaries; Historic buildings; Palms; Lakes and ponds; Photograph; Landscape photographs; Barbados--Saint John